Pengaruh Kepemilikan Manajerial, Dewan Komisaris, dan Komite Audit terhadap Fraudulent Financial Statements - Ihsanti, Mutiara; Cheisviyanny, Charoline (Universitas Negeri Padang, 2023)
This research aims to obtain empirical evidence and analyze the influence of managerial ownership, board of commissioners and audit committee on fraudulent financial statements in pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange 2018-2022. The population in this study were 12 pharmaceutical companies, while the sample in this study was 45 companies. This research uses secondary data obtained from the official website of the Indonesia Stock Exchange (BEI), namely www.idx.co.id, the BEI corner (Indonesia Stock Exchange) and company websites using the logistic regression analysis method. The results of this research conclude the managerial ownership, board of commissioners and audit committee have no effect on fraudulent financial statements.